Aerosolterapia y su impacto en el tratamiento de la neumonía intrahospitalaria en pacientes del Hospital de Infectología de la Ciudad de Guayaquil, durante el periodo mayo - septiembre del 2019 - Velásquez Constante, Víctor Manuel (2019)
Nosocomial or in-hospital pneumonia is considered as a pulmonary inflammatory process caused by an infection, this is absent at the time of admission of the patient to the hospital, this research project has as its main objective, Determine the impact of aerosol therapy in the treatment of in-hospital pneumonia In patients of the hospital of infectology of the city of Guayaquil, during the period May - September of 2019, the methodology used is based on the application of the Logical Historical Methods, and Method of analysis which leads us to the results of the research in where we found that the use of aerosol therapy is the first treatment in this disease, since the administration of nebulized drugs is more effective, this leads us to the conclusion that 97% of patients who used aerosol therapy have favored the restoration of health, which leads us to prepare a proposal whose subject is to prepare an informative workshop on the prevention and care of in-hospital pneumonia in patients of the infectology hospital of the city of Guayaquil, where the incidence of in-hospital pneumonia is expected to decrease, this will help patients to be in better conditions during your hospital stay.